BS ISO 24687. Fine ceramics (advanced ceramics, advanced technical ceramics). Measurement of Seebeck coefficient and electrical conductivity of bulk-type thermoelectric materials at room and high temperatures. (14th April 2022) - British Standards Institution,
No abstract available